2013
DOI: 10.1073/pnas.1303916110
|View full text |Cite
|
Sign up to set email alerts
|

Farnesylation of lamin B1 is important for retention of nuclear chromatin during neuronal migration

Abstract: The role of protein farnesylation in lamin A biogenesis and the pathogenesis of progeria has been studied in considerable detail, but the importance of farnesylation for the B-type lamins, lamin B1 and lamin B2, has received little attention. Lamins B1 and B2 are expressed in nearly every cell type from the earliest stages of development, and they have been implicated in a variety of functions within the cell nucleus. To assess the importance of protein farnesylation for B-type lamins, we created knock-in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 54 publications
2
83
0
Order By: Relevance
“…Three of the nuclear lamins (prelamin A, lamin B1, and lamin B2) are modified by a farnesyl lipid. In the case of lamin B1, this lipid modification is crucial for the migration of neurons in the developing brain (37). For other cell types, for example, keratinocytes, the importance of lamin farnesylation is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the nuclear lamins (prelamin A, lamin B1, and lamin B2) are modified by a farnesyl lipid. In the case of lamin B1, this lipid modification is crucial for the migration of neurons in the developing brain (37). For other cell types, for example, keratinocytes, the importance of lamin farnesylation is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Prelamin A, lamin B1, and lamin B2 are farnesylated proteins. Cell culture studies have suggested that the farnesylation of nuclear lamins is important for targeting those proteins to the nuclear envelope (14)(15)(16)(17)(18), and an absence of lamin B1 farnesylation causes severe neurodevelopmental abnormalities (37). One…”
Section: Lmnb1mentioning
confidence: 99%
“…In mice, B-type lamins have been shown to be essential for neuronal migration, whereby loss of B-type lamins causes lissencephaly-like defects in cortical development [84][85][86]. This has led to the prediction that whole-exome sequencing on patients with severe neurological diseases will eventually uncover nonsense and missense mutations in LMNB1 and LMNB2 [85].…”
Section: Central Nervous System Disordersmentioning
confidence: 99%
“…Second, the importance of protein farnesylation is different for lamin B1 and lamin B2. Jung et al 29 generated knock-in mice that produced nonfarnesylated versions of lamin B1 and lamin B2 (by replacing the cysteine of the CaaX motif with a serine). Knock-in mice expressing nonfarnesylated lamin B2 were healthy, fertile, and free of behavioral abnormalities; neither neuropathology nor nuclear shape abnormalities were detected in the cerebral cortex.…”
mentioning
confidence: 99%
“…Dumbbell-shaped nuclei were also found in cultured neurons as they migrated away from neurospheres. Jung et al 29 suggested that dumbbell-shaped nuclei were the consequence of defective anchoring of lamin B1 to the inner nuclear membrane and honeycombing of the nuclear lamina. They proposed that, during nucleokinesis, the lamina was pulled into the leading edge of the cell in a normal fashion, but the nuclear chromatin did not "come along for the ride."…”
mentioning
confidence: 99%